Manipulation of growth & meat quality by vitamin D and its analogues - Craggs, Lucinda (2010)
Recent published work indicates a role for pre-slaughter dietary vitamin D supplementation to promote post mortem meat tenderization in cattle (Montgomery et al., 2000; Foote et al., 2004; Montogmery et al., 2004), pigs (Wilborn et al., 2004) and sheep (Wiegand et al., 2001; Boleman et al., 2004). The hypothesis being that vitamin D supplementation at supra-nutritional levels is able to cause increases in the calcium status of the animals, increasing the activity of the calcium-dependant proteolytic enzymes, the calpains, which are responsible for meat tenderization (Koohmaraie & Geesink, 2006). Muscle fibre type is a variable factor in muscle and is related to meat quality (Klont et al., 1998). Vitamin D has been suggested to play a role in regulating skeletal muscle function through the creation of vitamin D receptor knockout mice models (Endo et al., 2003) and observations that muscle weakness and falling risk in vitamin D deficient patients is linked to a loss of fast muscle fibres (Aniansson et al., 1986; Larsson et al., 1979; Sorenson et al., 1979; Sato et al., 2005).